2020
DOI: 10.1002/kjm2.12149
|View full text |Cite
|
Sign up to set email alerts
|

miR‐335 modulates Numb alternative splicing via targeting RBM10 in endometrial cancer

Abstract: Numb is a conserved protein plays important roles in the development of cancer. Two Numb isoforms have been found produced by alternative splicing and play contrast roles in regulating cellular functions. It is reported that the expression of Numb long isoform (Numb‐L) was increased in various kinds of cancers, but in endometrial cancer, the condition is still unknown. The level of two Numb transcripts and protein isoforms were detected by semiquantitative polymerase chain reaction and immunoblotting in 47 pai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 26 publications
(52 reference statements)
0
15
0
Order By: Relevance
“…Improved diagnosis, risk assessment, and treatment strategies based on miRNA represents a promising area but will require future research. miR-193a-3p X [109] miR-193a-5p X [169] miR-193b X [129] miR-194 X X [128,179,180] miR-195 X [118,169] miR-196a-5p X [119] miR-196b X [169] miR-197 X [87] miR-198 X [169] miR-199a-5p X [169] miR-199b-5p X [117,125,169] miR-199b-3p X [125,169] miR-199b X [121] miR-299-5p X [169] miR-301 X [51,128] miR-302a-5p X [91] miR-320a X [33] miR-325 X [128] miR-326 X X [110,128] miR-328-3p X [119] miR-330 X [128] miR-330-3p X [169] miR-331 X [54] miR-331-3p X [69] miR-335 X [39] miR-337-3p X [119] miR-337-5p X [117,169] miR-340-5p X [33] miR-361 X [66] miR-363 X [129] miR-368 X [129] miR-369 X [126] miR-370 X [117] miR-371-5p X [169] miR-373 X [97] miR-375 X…”
Section: Discussionmentioning
confidence: 99%
“…Improved diagnosis, risk assessment, and treatment strategies based on miRNA represents a promising area but will require future research. miR-193a-3p X [109] miR-193a-5p X [169] miR-193b X [129] miR-194 X X [128,179,180] miR-195 X [118,169] miR-196a-5p X [119] miR-196b X [169] miR-197 X [87] miR-198 X [169] miR-199a-5p X [169] miR-199b-5p X [117,125,169] miR-199b-3p X [125,169] miR-199b X [121] miR-299-5p X [169] miR-301 X [51,128] miR-302a-5p X [91] miR-320a X [33] miR-325 X [128] miR-326 X X [110,128] miR-328-3p X [119] miR-330 X [128] miR-330-3p X [169] miR-331 X [54] miR-331-3p X [69] miR-335 X [39] miR-337-3p X [119] miR-337-5p X [117,169] miR-340-5p X [33] miR-361 X [66] miR-363 X [129] miR-368 X [129] miR-369 X [126] miR-370 X [117] miR-371-5p X [169] miR-373 X [97] miR-375 X…”
Section: Discussionmentioning
confidence: 99%
“…When RBM10 expression is downregulated, Numb is also downregulated, which can lead to the activation of the Notch pathway, enhanced HeLa cell lines colony formation, and promotion of tumor growth and proliferation ( 40 ). Additionally, miR-335 overexpression regulates the expression of Numb-L in endometrial carcinoma by targeting RBM10, providing a new biomarker for the diagnosis of endometrial cancer ( 41 ).…”
Section: Roles Of Rna-binding Motif Protein 10 In Regulating Tumor Dementioning
confidence: 99%
“…The miR-335 expression is increased in endometrial tumor tissues and negatively correlated with RBM10 protein levels. However, there was no significant change in the level of RBM10 mRNA, suggesting that the expression of RBM10 may be regulated by post-transcriptional regulatory factors such as miRNAs ( 41 ). Angiogenesis plays an essential role in the pathogenesis of gynecological diseases such as endometriosis and malignant tumor.…”
Section: Rna-binding Motif Protein 10 and Its Role In Human Diseasementioning
confidence: 99%
“…Especially, RBM10 has been shown to act as a regulator of alternative splicing [34,117]. A recent study showed that miR-335 modulates Numb alternative splicing via targeting RBM10 in endometrial cancer [118]. In this family, RBM10 shares a highly similar RNA-binding motif and a 30-50% amino acid sequence identity, with two other members, RBM5 and RBM6 [35].…”
Section: Tumor Suppressive Functions Of Rbm10 In Cancer Cellsmentioning
confidence: 99%
“…Mechanistically, RBM10 can induce tumor necrosis factor alpha (TNF-α) and apoptosis [132]. Moreover, it has been recently shown to suppress cancer cell proliferation through its function in alternative splicing of oncogenic mRNAs, such as NUMB [118] and VEGFA [32], or by inhibiting RAP1/AKT/CREB signaling [133]. Furthermore, our recent study showed that over expression of RBM10 reduces cancer cell migration and the EMT related gene Vimentin as well [134].…”
Section: Tumor Suppressive Functions Of Rbm10 In Cancer Cellsmentioning
confidence: 99%